A Simple and Easy Process for the Determination of Estimated Plasma Glucose Level in Patients Presenting to Hospital: An Example of Multicentric Data Mining. (December 2016) - Serdar, Muhittin A.; Koldaş, Macit; Serteser, Mustafa; Akın, Okhan; Sonmez, Cigdem; Gülbahar, Ozlem; Akbıyık, Filiz; Ünsal, Ibrahim
The aim of the present study was to determine the relation between the simultaneous fasting plasma glucose level and HbA1c in a large population of patients presenting to the hospital, based on various measurement methods available for HbA1c. HbA1c levels of 162, 210 patients presenting to various hospitals and laboratories were measured based on seven different systems, and at the same time, eAG levels were calculated based on HbA1c levels. The correlation coefficients ( r ) between serum plasma glucose and HbA1c levels were found to be 0.809, 0.774, 0.779, 0.817, 0.704, 0.796, and 0.747 in Bio-Rad Variant II, Tosoh G8, ADAMS A1c, Trinity Boronate Affinity, Chromsystems HPLC, Roche Tina-quant, and Abbott Architect, respectively. The concordance correlation coefficients between the eAG levels as calculated with the formulas provided in the text and the eAG levels as calculated according to NGSP directions (where eAG = (28.7*HbA1c) – 46.7) were found to be between 0.9339 and 0.9866. Despite the progress made for the standardization of HbA1c measurements, the relation between serum glucose and HbA1c still demonstrated certain discrepancies pertaining to the differences in measurement methodologies. As a conclusion, each laboratory could determine different eAG levels depending on the data originated by their individual analyzer.